Guidance and Counseling In Higher Education - Een Khomariyah; Hafsah Al Mahpudzoh; Siti Anjeli (P3M STAI Kuningan, 2023)
The purpose of writing is to describe the availability of guidance and counseling facilities and infrastructure in universities. One of the successes of guidance and counseling services is supported by adequate infrastructure facilities. This study technique uses a literature review or library research. The conclusion is that guidance and counseling services in universities have orientation services, information services, placement and distribution services, content mastery services, individual counseling services (individual), Group Guidance and Group Counseling services, Group Guidance (BKp), and Group Counseling (KKp). consulting services, mediation services, and advocacy services. and assistance services provided to students include providing guidance assistance in personal, social, study, and career fields.